Model Mental Siswa dalam Argument Driven Inquiry Berbasis Fenomena Disertai Penilaian Formatif pada Materi Hukum Newton - Jamiatul Mufidah; Parno Parno; Markus Diantoro (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purpose of this study is to describe students' mental models in phenomenon-based Argument Driven Inquiry (ADI) learning with formative assessment. This research uses quantitative and qualitative approaches with mixed methods of embedded experimental model design. The subject was taken from X IPA-1 with 26 students at Pademawu 1 Public High School. The instrument was developed in the form of 6 essay questions. Research data were analyzed using t-paired test, N-gain, and effect size. The results are categorized as surface, matching, and deep type of mental models. It is found that the phenomenon-based ADI accompanied formative assessment affect significantly on the mental models of students with an effect size of 1.86. It is also reveald that the improvement of students' mental models is low category with an N-gain of 0.2.Abstrak: Tujuan penelitian adalah mendiskripsikan model mental siswa dalam pembelajaran Argument Driven Inquiry (ADI) berbasis fenomena disertai penilaian formatif. Penelitian ini menggunakan pendekatan kuantitatif dan kualitatif dengan mixed method desain embedded experimental model. Subjek penelitian X IPA-1 dengan 26 siswa di SMAN 1 Pademawu. Instrumen penelitian berupa enam soal uraian. Data penelitian dianalisis dengan menggunakan t-paired test, N-gain, dan effect size. Hasil penelitian dikategorikan dalam tiga tipe model mental surface, matching, dan deep. Hasil penilitian didapatkan bahwa ADI berbasis fenomena disertai penilaian formatif berpengaruh kuat terhadap model mental siswa dengan nilai effect size 1.86. Selain itu diperoleh informasi bahwa peningkatan model mental siswa dalam kategori rendah dengan nilai N-gain 0.2.